PENGARUH KOMPENSASI MANAJEMAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK PERUSAHAAN - Dhina Kristina; Eny Suprapti; Thoufan Nur (Universitas Muhammadiyah Malang, 2018)
This study examines corporate governance influencing tax management behavior and contributes to the literature on corporate governance. This research is management compensation and corporate corporate governance mechanism, in managing taxes to improve performance. This study found that there was a significant positive effect on management compensation variables in corporate tax management in manufacturing companies listed on the Indonesia Stock Exchange. There is a significant positive effect on the variable Corporate Governance on corporate tax management in Manufacturing companies listed on the Indonesia Stock Exchange. Management compensation has a dominant influence on corporate tax management in Manufacturing companies listed on the Indonesia Stock Exchange.